Capital structure and performance of Islamic banks: determinants and optimality - al-Kayed, Lama Tarek (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2012)
As new comers to the market, Islamic Banks (IBs) are facing a trade-off. They can either employ high capital ratios which increase the soundness and safety of the bank and lowers the required return (risk) by investors, or depend on deposits and Islamic bonds which are considered cheaper sources of funds due to their tax deductibility. IBs' management must carefully decide upon the appropriate mix of debt and equity, namely, capital structure, in order to maximize the value of the bank. This study examines the effect of capital structure on IBs' performance in an attempt to provide guidance to managers in the issue of raising capital. The study also examines whether regulatory capital requirements are the first-order determinants of IBs' capital decisions. Furthermore, the study calculates the optimal capital structure for the sample IBs and uses it as guidance for capital structure decisions. Using a sample of 85 IBs covering 19 banking systems, the study uses a Two-Stage Least Squares (2SLS) method to examine the performance determinants of IBs' in order to control for the reverse causality from performance to capital structure and uses the Ordinary Least Squares (OLS) method to examine the determinants of IBs' capital structure. After controlling for macroeconomic environment, financial market structure and taxation, results indicate that IBs' performance (profitability) measures respond positively to increases in equity (capital ratio). The result is consistent with the signaling theory which predicts that banks expected to have better performance credibly transmit this information through higher capital. As for the reverse causation from performance to capital structure, results indicate that more profitable IBs employ higher leverage. This is consistent with the efficiency-risk hypothesis which predicts that more profitable firms choose lower equity ratios (higher leverage). Risk is found to be an insignificant factor in determining leverage, which indicates that minimum capital requirements are not first-order determinants of IBs' capital structure and that standard determinants of capital structure can explain variation in IBs' book capital. Results of optimal capital structure finds that the capital-asset ratio has an increasing effect on IBs' profitability. The optimal capital ratio is found to be 37.41%. At capital ratios below 37.41% equity is expensive and has a negative effect on return on equity (ROE) due to the higher required return by investors. Beyond 37.41% equity starts to have a positive effect on ROE and becomes a cheap source of financing. As a general guide, IBs should have minimum capital ratios of 37.41% to be viewed as safe and sound by investors and to lower the cost of issuing additional equity.